Seismic reflection profile AWI-98580, Arctic Ocean - Weigelt, Estella; Geissler, Wolfram H (PANGAEA, 2024)
The data set provides unprocessed and processed seismic reflection data collected during Expedition PS51 (ARK-XIV/1a) onboard RV Polarstern in the central and Arctic Ocean along the Lomonosov Ridge in 1998. Detailed data acquisition parameters for the profiles are documented in the expedition report (Jokat, 1999). Metadata, recording parameters, and the seismic data processing sequence are documented in the EBCDIC-Headers enclosed in the seg-y files. Navigation information is included in the seg-y headers, and in the CDP-SHOT-latitude-longitude file (see data product). A ReadMe file additionally lists the metadata and recording parameters for the seismic profile. The data set is grouped into three categories: 1. Raw data comprise (a) demultiplexed seismic data in seg-y format, (b) a shot list of date, time and shot-number, and (c) navigation data with date, time, and coordinates. 2. Primary data consist of (a) CDP-sorted data in seg-y format, and (b) navigational data in a conventional UKOOA- file. 3. The data product is provided as (a) stacked version of the seismic profile in seg-y format and (b) a list with CDP and SHOT numbers as well as geographical coordinates. Please note that the low-frequency reflector that parallels the sea floor at depths of about 190 ms two-way traveltime (~150 m) is an artifact which has not been removed.
Keywords: Arctic Ocean; AWI Geophysics; Polarstern; Seismic reflection data